Nitrosyl Tetrafluoroborate Catalyzed Preparation of 2,3-Unsaturated Glycosides and 2-Deoxyglycosides of Hindered Alcohols, Thiols, and Sulfonamides - Santra, Abhishek; Guchhait, Goutam; Misra, Anup Kumar (Synlett, 2013)
Nitrosyl tetrafluoroborate (NOBF4) has been successfully applied as an efficient organocatalyst for the preparation of 2,3-unsaturated and 2-deoxyglycosides of hindered alcohols, aryl thiols, and aryl sulfonamides from glycal derivatives under the Ferrier rearrangement conditions. Product yields and stereo-outcomes were very good.
Keywords: glycal; Ferrier rearrangement; NOBF4; 2,3-unsaturated glycoside; 2-deoxyglycoside